Syariâah, Fiqih dan Sebuah Perspektif tentang Tarjîh - Huda, Miftahul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
This paper takes into account the very fact that Syariâah has been a subject of controversy over centuries. Its interpretation in the form of fiqh (Islamic jurisprudence) is a strong indication that Syariâah is not immune from personal subjectivication. Fiqh is quite personal whereby a jurist would read the message of Syariâah and attempt to give his personal and subjective interpretation of it. Nonetheless, the paper is also of the argument that this controversy is in itself a source of the dynamics of Syariâah. It is due to this controversyâotherwise known as the legal dispute- that fiqh is capable of being developed over times. Some substances of fiqh are responses to the opposing views on some issues. Not less important than this is to delve into the factors that triggered such controversy and dispute. The paper speaks of three factors, namely the nature of subject-matter, the way the jurists interpret it, and the social circumstances that surround the jurists and help shape their way of thinking. The first is epistemological, the second methodological, whereas the third to sociological. The three factors are inter-related and form as it were the comprehensive legal products which the Muslims currently inherited. The Tarjih in the meantime, is a form of a legal product, which serves both as a social and intellectual modality for the Muslims in their daily lives.